Nilai Islam Dalam Praktik Keperawatan: A Sistematic Review - Haeril Amir (FORIKES, 2020)
Background: Islamic Value is an important component in the concept of Islamic nursing, Islamic values can be classified into spiritual values, altruistic values and the value of respecting and understanding others. Aim: The aim of the study is to present and highlight the importance of Islamic values in nursing practice. Method: Extensive review of the recent literature was conducted in electronic databases Pubmed, Science Direct, Wiley Online using the appropriate key words Nursing, Islamic Value. Result: Islamic values in nursing practice are found and very useful, Spiritual care can facilitate healing, life satisfaction, recovery, and quality in patients in the terminal or chronic phase. Islamic values are the foundation of every religion, spiritual provide comfort in everyday life. Conclusion: Islamic values are useful in nursing practice because Islamic value talk a lot about the lives of fellow humans, healing disease and respect and understand others. Keywords: Islamic value; spiritual; altruistic; nursing practice ABSTRAK Latar Belakang: Nilai Islam merupakan komponen penting dalam konsep keperawatan Islam, nilai-nilai Islam dapat diklasifikasikan menjadi nilai spiritual, nilai altruistik dan nilai menghormati dan memahami orang lain. Tujuan: Tujuan dari penelitian ini adalah untuk menyajikan dan menyoroti pentingnya nilai-nilai Islam dalam praktik keperawatan. Metode: Tinjauan luas literatur terbaru dilakukan di database elektronik Pubmed, Science Direct, Wiley Online menggunakan kata kunci Keperawatan, Nilai Islami. Hasil: Nilai-nilai Islam dalam praktik keperawatan ditemukan dan sangat berguna, perawatan spiritual dapat memfasilitasi penyembuhan, kepuasan hidup, pemulihan, dan kualitas pada pasien dalam fase terminal atau kronis. Nilai-nilai Islam adalah dasar dari setiap agama, spiritual memberikan kenyamanan dalam kehidupan sehari-hari. Kesimpulan: Nilai-nilai Islam berguna dalam praktik keperawatan karena nilai-nilai Islam banyak berbicara tentang kehidupan sesama manusia, menyembuhkan penyakit dan menghormati serta memahami orang lain Kata Kunci: nilai Islam; spiritual; altruistik; praktik keperawatan.